Pengaruh Diskon, Gratis Ongkos Kirim dan Promosi Terhadap Keputusan Pembelian di Marketplace Shopee(Survei pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Slamet Riyadi Surakarta) - Windi Hananta; Sumaryanto (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of discounts, free shipping, and promotions on consumer purchasing decisions on the Shopee e-commerce platform. The research background is based on the increasingly fierce competition in the e-commerce industry in Indonesia, which demands companies to develop effective marketing strategies to attract consumers. The data used in this study are quantitative and qualitative. The data sources used are primary and secondary data. The sample size for this study was 100 active Shopee users. The sampling method used was purposive sampling. Data collection used a questionnaire using Google Forms. Data analysis was performed using multiple linear regression using validity and reliability tests, classical assumptions, and hypothesis testing. The results indicate that discounts, free shipping, and promotions simultaneously have a significant positive effect on consumer purchasing decisions. Partially, discounts and promotions have a significant positive effect, while free shipping has a positive but smaller effect than the other two variables. The Adjusted R Square value of 0.464 indicates that 46.4% of the variation in purchasing decisions can be explained by these three independent variables, with the remainder influenced by factors outside the research model. These findings confirm that incentive-based marketing strategies such as discounts, promotions, and free shipping are important factors in influencing purchasing decisions, especially on the Shopee platform.